Model for the characterization of epidemies generated by the vector Aedes aegyypti. Case study: Norte de Santander Department, Colombia (2018)
Applied technologies to health systems have been noticed as a required tool to reduce the reappearance rate of certain illnesses, to identify groups of risk or to involve the patient in the care of his own health. Taking in consideration the fact that in the North Santander Department the occurrence of the outbreak of illnesses transmitted by the vector Aedes aegypti shows intense increase since its re-emergency in 2014, with the presence of several manifestations, one of the most likely solutions to prevent the illness, is the epidemiologic surveillance alongside the strategic prevention/ control of the vector. In this context, this project was developed with the purpose of characterize patients by the building of a knowledge database for digital health that allows to create an architecture to integrate, analyze and structure the historical data according to the detected cases, in order to collect the information from the direct field, store it and process it, to present reports and knowledge models with the right indicators that allow to look out often the symptoms and to control the increase of such epidemies.